Trade union revitalisation in South Africa: Green shoots or false dawns? - Devan Pillay (International Labour Organization (ILO), 2017)
In South Africa a growing crisis of political legitimacy - given widening social inequality, high unemployment, persistent poverty, ecological devastation and increased corruption - has had a direct impact on the union movement. The National Union of Metalworkers of South Africa's (NUMSA's) 2013 decision to break away from the alliance with the ruling African National Congress (ANC) and SA Communist Party (SACP), and build a broad united front and a 'movement for socialism', was momentous. Enthusiastic observers likened it to the 1973 'Durban moment', where a massive strike wave precipitated the re-emergence of independent, radical trade unionism in South Africa. This 'moment' was preceded by an equally signficant yet under-appreciated 'moment' - the path-breaking work on climate change and renewable energy. NUMSA decided in 2013 to draw together a wide range of left movements and activists, and in that process debate the character and form of a new movement that would challenge the hegemony of the ANC and SACP, as well as provide a clearer leftwing alternative to the racialpopulist Economic Freedom Fighters (EFF). Taken together, these two moments were hopeful expressions (or green shoots) of a new type of 21st century, democratic 'ecosocialist' working class politics. The subsequent launch of the SA Federation of Trade Unions (SAFTU) in April 2017 was meant to give this momentum a further boost. This paper argues that the promise of trade union revitalisation is fraught with difficulty. Indeed, as NUMSA retreats into its shell of 20th century orthodoxy, many fear that what seemed like green shoots of revitalisation were, in fact, false dawns.
Keywords: 330